PENERAPAN PROGRAM MADRASAH DINIYAH DALAM MENINGKATKAN PENGETAHUAN DAN PENGAMALAN AJARAN ISLAM DI SMP NURUL JADID - Faizatul Widat; Arofa Mukhalik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the Madrasah Diniyah program at Nurul Jadid Paiton Junior High School and its impact on increasing knowledge and practice of Islamic teachings among students. The Madrasah Diniyah program is designed to deepen the understanding of Islam beyond formal class hours, focusing on teaching the Qur'an, fiqh, morals, and Islamic history. The research method used is a qualitative approach with case studies, which involves in-depth interviews, observations, and documentation analysis. The results of the study show that the implementation of this program has succeeded in increasing students' religious knowledge, especially in reading the Qur'an with correct tajweed, as well as deepening their understanding of fiqh and morals. In addition, this program also has a positive impact on the practice of Islamic teachings in students' daily lives, which is reflected in more disciplined, polite, and caring behavior towards others. The improvement of students' character to be more responsible, independent, and time-respecting is one of the significant outcomes of this program. Overall, the implementation of the Madrasah Diniyah program at Nurul Jadid Paiton Junior High School has proven to be effective in improving religious knowledge and character formation of students, which is very relevant to the challenges of modern times. This program is expected to be a model for other schools in implementing comprehensive and applicable religious education.